(3QMdI EHQGgGe HGQShfR ef MdH Edi GdNdjL GdYQHj (B(1774-1775) /s - (3HGQShfR, CHQGgGes 1785-; (3eMehO, CfjS YHO GdNGdbs; (3HGQShfR, EHQGgGe,s 1785-. ((3HjQhJ (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ ,s (3YeGf (B- (3GdCQOf (B:s (3OGQ GdaGQS ,s, 2013)
(3aj gPG GdcJGH jbOe HGQShfR JaGUjd Yf GdJLGQI aj GdEScfOQhfI, hYf GdeOjfI hVhGMjgG hYf GdQ MdGJ GdJj bGe HgG aj GdefWbI, hhUa ddeOf hGdbQi hGdWQb GdCNQi GdJj eQ HgG hUaG ObjbG, agh HUaJg bfUdG GgJe HhUa CSdhH eYjTI GdbfGUd GdCNQi(B. (3haj CKfGA eQhQg HUMQGA GdHGOjI GdShQjI aj SfI (B(1774) (3SLd hUaG eaUdG heaYeG HGdMjhjI ddefGWb GdeeJOI ef MdH Edi HZOGO hcGf hUag ddbGadI CKfGA GdJQMGd ef CQhY eG cJH Yf MjGI GdHGOjI, haj cd ehVY ef ehGVY GdQMdI fTgO GgJeGeG cHjQG HGdJLGQI hHGdMcheI hCSGdjH GdYjT(B. s
Keywords: (3HGQShfR,CHQGgGes -- 1785- -- (3QMdGJs -- (3Ohd GdNdjL GdYQHjIs; (3HGQShfR,CHQGgGes -- 1785- -- (3QMdGJs -- (3ShQjGs -- (3MdHs; (3QMdGJs -- (3GdNdjL GdYQHjs -- (3MdH (B- (3ShQjGs -- (3bQf (B18s